(untitled) (Research, Society and Development, 2021)
Quinoa stands out for its high nutritional potential and its ability to adapt to different environments. However, seed quality is one of the main factors to be considered when implanting the crop, so it becomes important to complement the information provided by the germination test through vigor tests. Thus, the objective was to adapt the methodology of the electrical conductivity test to assess the physiological quality of quinoa seeds. The initial characterization of the seed lots was carried out through the initial water content, mass of a thousand seeds, germination and seedling emergence tests in commercial substrate. For the electrical conductivity test, four seed lots (genotype Q13-31) were grown in the 2016/2017 and 2017/2018 seasons, using 25, 50 and 75 seeds, at 20º C, in volumes of deionized water (25 and 50 mL), for periods of imbibition (1, 2, 3, 4 and 5 h). The design was completely randomized, the means analyzed by the Scott-Knott test. A simple correlation analysis was carried out between electrical conductivity and germination and seedling emergence tests. The electrical conductivity test conducted with 50 seeds soaked in 50 mL of deionized water, for 2 h, is efficient for the evaluation of the physiological potential of the quinoa seed lots, in addition to presenting significant correlations with the emergency test.